A Note Concerning Hamilton Cycles in Some Classes of Grid Graphs - A. N.M. Salman; E. T. Baskoro; H. J. Broersma (Institute for Research and Community Services (LPPM) ITB, 2003)
A graph G is called hamiltonian if it contains a Hamilton cycle, i.e. a cycle containing all vertices. Deciding whether a given graph has a Hamilton cycle is an NP-complete problem. But, it is a polynomial problem within some special graph classes. In this paper we consider three classes of grid graphs, namely rectangular grid graph, eta grid graph and omega grid graph. Our main result characterizes which of these graphs are hamiltonian.